IMPROVING THE PERFORMANCE OF VILLAGE Secretary-BaSed Financial incentiveS, training and Monitoring, and EVALUATION (Case Study on The Government of Demak Regency) - Sukarman Sukarman (IJIBE (International Journal of Islamic Business Ethics), 2017)
The present study aimed to test a model in which training predicts professional competence and village secretary performance that moderated by money incentive and monitoring and evaluating. A total of 164 respondents from the Village Government Office of Demak Regency completed questionnaires on training, professional competence, money incentive, monitoring and evaluating, and village secretary performance. Results from structural equation modeling based smartPLS 3.0 confirmed that 1) training was positively related to professional competence and village secretary performance; 2) professional competence was positively related to village secretary performance; and 3) money incentive and monitoring and evaluatingmoderated the relationships between training and village secretary performance.Keywords : Training, Professional competence, Money incentive, Monitoring and evaluating, Village secretary performance.